Clinical features of monoclonal gammopathy of renal significance related renal lesions - Xiao-jing Wu; Xin Li; Mu-yin Zhang; Li-li Xu; Xu Hao; Wei-ming Wang (Linchuang shenzangbing zazhi)
ObjectiveTo explore the clinical features and pathological spectrum of monoclonal gammopathy of renal significance （MGRS） related renal lesions and search for valuable clinical parameters aiding in their differential diagnoses.MethodsFrom January 2014 to February 2021， medical records and clinicopathological data were reviewed for MGRS patients with associated renal lesions as determined by renal pathology. Monoclonal gammopathy of undetermined significance （MGUS） patients complicated with kidney disease hospitalized during the same period were selected as control group.ResultsMGRS associated renal lesions included light chain amyloidosis （n=34）， light chain deposition disease （n=3）， proliferative glomerulonephritis with monoclonal Ig deposits （PGNMID， n=2）， cast nephropathy （n=2）， thrombotic microangiopathy （TMA， n=1）， cryoglobulin glomerulonephritis （n=1） and fibroglomerulonephritis （n=1）. Patients with amyloidosis significantly had a lower proportion of hypertension （23.5% vs 80.0%， P=0.002） and a higher proportion of nephrotic syndrome （85.3% vs 40.0%， P=0.008） than nonamyloidotic MGRS group. In light chain amyloidosis， the types of serum intact Ig were predominantly IgG （61.9%） and a major type of serum light chain was λ （89.7%）. In LCDD， a major type of serum light chain was k. As compared with MGUS group， MGRS group had a lower positive rate of serum immunofixation electrophoresis （IFE， 70.5% vs 100%， P=0.005）， a higher abnormal rate of serum free light chain （FLC） ratio （63.2% vs 25.0%， P=0.038） and a higher proportion of hypocomplementaemia （40.9% vs 14.3%， P=0.032）. No significant inter-group difference existed in positive rate of urinary IFE （P=0.195）. The sensitivity of abnormal FLC ratio for diagnosing MGRS was 63.2% with a specificity of 75% and overall accuracy of 67.7%. AUC （area under curve） and 95% CI of abnormal plasma cell ratio in BM for diagnosing MGRS were 0.855（0.719-0.991）. The sensitivity， specificity and overall accuracy of abnormal plasma cell ratio ≥0.55% were 83.3%， 80% and 82.5% respectively.ConclusionThe most common pathological type of MGRS related renal lesion is amyloidosis λ type. Hypocomplementaemia， abnormal FLC ratio and abnormal plasma cells in BM boost the probability of detecting MGRS lesions during renal biopsy.